Genetically-Mediated Associations between Measures of Childhood Character and Academic Achievement - Tucker-Drob, Elliot M. (J Pers Soc Psychol, 2016)
Researchers and the general public have become increasingly intrigued by the roles that systematic tendencies toward thinking, feeling, and behaving might play in academic achievement. Some measures belonging to this group have been well studied in genetics and psychometrics, while much less is known about other measures. The current study focuses on seven such character traits prominently featured in influential intervention-oriented and/or socialization theories of academic achievement: grit, intellectual curiosity, ability self-concept, mastery orientation, educational value, intelligence mindset, and test motivation. In a population-based sample of 811 school-aged twins and triplets from the Texas Twin Project, we tested (a) how each measure relates to indices of the Big Five personality traits, (b) how the measures relate to one another, (c) the extent to which each measure is associated with genetic and environmental influences and whether such influences operate through common dimensions of individual differences, and (d) the extent to which genetic and environmental factors mediate the relations between fluid intelligence, character measures, and academic achievement. We find moderate relations among the measures that can be captured by a highly heritable common dimension representing a mixture of Openness and Conscientiousness. Moreover, genetically-influenced variance in the character measures is associated with multiple measures of verbal knowledge and academic achievement, even after controlling for fluid intelligence. In contrast, environmentally-influenced variance in character is largely unrelated to knowledge and achievement outcomes. We propose that character measures popularly used in education may be best conceptualized as indexing facets of personality that are of particular relevance to academic achievement.